Cultivating a culture of sustainability: A review of UK higher education institutions engagement with business for the delivery of responsible management education by Emma Tarrant Tayou 2021 - Tayou, Emma Tarrant (2021)

(untitled)
This study set out to answer the research questions of (1) how do UK Higher Education Institutions signatory to the UN PRME report on collaboration with businesses and business practitioners and (2) what are the types of collaborations that exist between HEI and businesses as reported on in the UN PRME Sharing information on Progress reports submitted between 2018 and 2021. The study involved secondary data collection via the review of 15 SIP reports and primary data in the form of semi-structured confirmatory interviews. The findings set out a wide range of engagement between HEIs and businesses, however reporting is inconsistent and thus further work is needed to understand the true extent of the volume of collaborative activity. The study ends with recommendations to standardise reporting styles and cycles for the PRME SIP reports and offers guidance for HEIs wishing to broaden and enhance collaborative activity in the delivery of responsible management education to their students.